Entrepreneurship Sustainable Business Practices and Corporate Social Responsibility as Added Value in Entrepreneurship - Setiawan, Wahyu Sandi; Fatimah, Fatimah; Kamaruddin, Syamsu A. (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This research conducts a comprehensive analysis of the literature on sustainable business practices and corporate social responsibility (CSR) through a combination of bibliometric analysis and qualitative exploration. This research aims to reveal the impact, trends and implementation strategies in the field. Bibliometric analysis uses VOS viewer to visualize influential authors, frequently cited works, thematic groups, and keyword distribution. Additionally, the qualitative investigation explores real-world implementation strategies used by organizations for sustainable business practices and CSR initiatives. Sustainable business practices and CSR have evolved from simply philanthropic efforts to become essential components of corporate strategy. By adopting environmentally conscious operations, responsible supply chain management, and innovative strategies, companies can minimize negative impacts on the environment while promoting social and economic benefits.